Social Norms Theory and Development Economics - Eriksson, Lina (World Bank, Washington, DC, 2015)
Social norms affect almost every aspect of people’s lives, and can be an obstacle to or support economic development. This paper outlines what social norms are and how they work, providing examples from everyday life and from development case studies. Sometimes not much can be done about changing undesirable social norms. In those cases, development economists need to be aware of how the existence of those norms can impact the effects of the policies they advocate. But of particular importance to development economists is the ways in which social norms can be changed, at least under some circumstances. Understanding of social norm change is still patchy at best, but the paper outlines the theoretical underpinnings of change, with empirical evidence from various policies aimed at changing social norms. However, some of those policies raise ethical concerns that would require attention.